Development of the inorganic nanoparticles reinforced alginate‐based hybrid fiber for wound care and healing. Issue 42 (2nd June 2021) - Weng, Lin; Zhang, Xiaolin; Fan, Wei; Lu, Yao
Abstract: It is necessary for wound dressing constructed from fibers capable of overcoming external stretching and protecting injured skin. The limited mechanical performance of existing alginate fiber limits its biomaterial application. Herein, this issue can be addressed via incorporation of uniformly dispersed hydroxyapatite (HAP) and silica (SiO2 ) nanoparticles (NPs) in alginate (Alg) by microfluidic spinning technique. These NPs serve as a reinforcing phase to help the alginate‐based composite to develop outstanding mechanics. Both HAP‐Alg and SiO2 ‐Alg hybrid fibers exhibited excellent breaking elongation, 67.56 ± 6.85% and 52.08 ± 5.20% respectively, while that of breaking strength were 7.04 ± 0.58 MPa and 4.96 ± 0.59 MPa. Furthermore, in vitro cytotoxicity was explored by studying on the proliferation and migration of keratinocytes and fibroblasts, which illustrated no obvious cytotoxicity of the resulting alginate fibers loaded with HAP and SiO2 NPs. The artificial scratch assay demonstrated that the resulting alginate‐based composite fiber can assist the injured skin regeneration. This work provides a significant progress in the conception of developing NPs reinforced alginate‐based hybrid fiber which can withstand the large strain behavior and facilitate wound healing, making it an ideal candidate as wound dressings and fibrous scaffolds. Abstract :